2007
DOI: 10.1007/s11071-006-9195-9
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic construction of nonlinear normal modes for continuous systems

Abstract: This paper provides a review of some asymptotic methods for construction of nonlinear normal modes for continuous system (NNMCS). Asymptotic methods of solving problems relating to NNMCS have been developed by many authors. The main features of this paper are that (i) it is devoted to the basic principles of asymptotic approaches for constructing of NNMCS; (ii) it deals with both traditional approaches and, less widely used, new approaches; and (iii) it pays a lot of attention to the analysis of widely used si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…The basic idea of this approach is a construction of certain particular selfsimilar solutions of a nonlinear problem, which can be considered as asymptotics of a wide class of other solutions. A realization of this approach for nonlinear dynamics of elastic systems (beams, plates, shallow shells) is presented by Andrianov and his coauthors [168][169][170][171][172]. The paper [172] is a survey of publications on the NNMs and similar solutions in nonlinear continuous elastic systems.…”
Section: Dynamics Of Piecewise Linear and Impact Systemsmentioning
confidence: 99%
“…The basic idea of this approach is a construction of certain particular selfsimilar solutions of a nonlinear problem, which can be considered as asymptotics of a wide class of other solutions. A realization of this approach for nonlinear dynamics of elastic systems (beams, plates, shallow shells) is presented by Andrianov and his coauthors [168][169][170][171][172]. The paper [172] is a survey of publications on the NNMs and similar solutions in nonlinear continuous elastic systems.…”
Section: Dynamics Of Piecewise Linear and Impact Systemsmentioning
confidence: 99%
“…Until 1991, the approach of determining the NNMs of a mechanical system was based on 'direct attack' to the equations of motion of the underlying conservative system by neglecting the dissipative forces, and their determination leads to the backbone curves of the system. Then by adding small damping (as it is true in structural mechanical systems) and periodic excitation, the FRFs in similar fashion can be determined with resonance points those that are very close to the backbone curves of the system; a review of these approaches in Adrianov (2008); Kerschen et al (2009); Mikhlin and Avramov (2010); Nayfeh (1995) can be found. A research relevant to NNMs that is straightforward related with the development of the theory in this article is by Vakakis PhD thesis of Vakakis (1991).…”
Section: Introductionmentioning
confidence: 99%
“…They generally rely on an asymptotic development for approximating the invariant manifold [6][7][8][9][10][11]. More recently, purely numerical methods have been proposed [12][13][14], but they are often restricted either by complexity (i.e.…”
Section: Introductionmentioning
confidence: 99%